Case Report: Good cardiac tolerance to Toripalimab in a CVD patient with oral melanoma - Pan, Wei; Yin, Li; Guo, Yadi; Pan, Dachao; Huang, Hui (Frontiers in Pharmacology, 2022)
Introduction: Primary oral melanoma is extremely rare, and the prognosis is very poor. With the development of immunotherapy, melanoma’s treatment landscape changed dramatically. Toripalimab, a recombinant Programmed death receptor 1 (PD-1) monoclonal antibody, has been approved as second-line therapy for metastatic melanoma. However, the cardiac toxicity of Toripalimab is seldom reported. This article describes the application of Toripalimab on a patient who suffered from Primary oral melanoma accompanied with mitral valve disease and arrhythmia. Case Summary: A 55-year-old Chinese female was diagnosed with BRAF wild-type oral malignant melanoma by excisional biopsy and genetic test. The melanoma was quickly progressed after complete tumor resection. Adjuvant therapy after surgical resection was applied to control the progression of melanoma. Due to this patient’s basic cardiovascular situation, sacubitril-valsartan, spironolactone, and bisoprolol were used to maintain cardiac function. After five anti-tumor treatment courses, we re-evaluate the patient systemically from the symptom, physical examination, and auxiliary examination. The result showed that the patient received Toripalimab combined with chemotherapy and radiotherapy did not present severe side-effects on the cardiovascular system. The cardiac function remained well. Conclusions: This case provided evidence of Toripalimab combined with chemotherapy on melanoma patients with complex cardiovascular diseases. Toripalimab demonstrated a manageable safety profile and durable clinical response. Besides, the standard CHF treatment plays a vital role in the protection of cardiac function. In a cancer patient with complex cardiovascular diseases, standard prophylactic CHF treatment should be applied at an early stage.